1992
DOI: 10.1111/j.1365-3024.1992.tb00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally acquired cellular and humoral immune responses to the major merozoite surface antigen (Pf MSP1) of Plasmodium falciparum are associated with reduced malaria morbidity

Abstract: We have investigated the pattern of acquired immune responses to the major surface protein of Plasmodium falciparum merozoites (gp 190, PfMSP1) in a malaria endemic population in West Africa. A prospective longitudinal study in 3- to 8-year-old children was conducted to examine the relationship between naturally acquired immune responses to PfMSP1 and subsequent susceptibility to malaria infection and clinical disease. A population cross-sectional survey was performed to investigate changes in immune response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
182
2
8

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(208 citation statements)
references
References 32 publications
16
182
2
8
Order By: Relevance
“…Genes encoding surface antigens targeted by the host's immune response are subject to diversifying selection promoting genetic polymorphism (44). There is evidence for diversifying selection acting on erythrocyte-binding antigens in P. vivax as well as P. falciparum (12).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding surface antigens targeted by the host's immune response are subject to diversifying selection promoting genetic polymorphism (44). There is evidence for diversifying selection acting on erythrocyte-binding antigens in P. vivax as well as P. falciparum (12).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a single microarray hybridization has added substantially to our list of candidate genes for testing as transmission blocking agents. It is noteworthy that MSP-1, a leading candidate for malaria vaccines (Holder, 1988;Riley et al, 1992), is one of the most prominent blood stage-speci®c transcripts identi®ed by microarray hybridization (Table 2A). Other transcripts from Table 2A may prove to be important new targets for asexual stage vaccines.…”
Section: Advantages Of the Shotgun Approachmentioning
confidence: 99%
“…The antagonizing effects of MSP-1 variants were observed in the majority (average 80%) of individuals from The Gambia who showed IFN-c responses. T cell proliferation to MSP-1 recombinant proteins has been reported to correlate with protection against clinical malaria in prospective field studies [22]. Therefore, the observed correlation of both IFN-c and proliferative immune interference with allelic epitopes M3/4 and M7/8 could potentially affect protective memory T cell effector functions.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that MSP-1 proliferative responses correlated with protection against clinical malaria [22]. Immune interference between allelic MSP-1 epitopes was further studied in assays of proliferation, set up in parallel with ex vivo IFN-c ELISPOT immune interference assays.…”
Section: Immune Interference Affects Both Proliferative T Cell Responmentioning
confidence: 99%